Mating success follows duet dancing in the Java sparrow - Soma, Masayo (PLoS One, 2017)
Mutual interactions between sexes have multiple signalling functions. Duet singing in songbirds is related to mutual mate guarding, joint resource defence, and signalling commitment. Coordinated visual displays of mating pairs are thought to perform similar functions, but are less well understood. The current study evaluated mutual interactions in an Estrildid species to explore the relative importance of duet dancing and male singing in mating success of pairs in a first encounter. When Java sparrows (Lonchura oryzivora) court prospective mates, only males sing. However, both males and females perform courtship dances, often in a duet-like manner. These dances are typically terminated by female copulation solicitation displays (CSDs). In the current study, we observed higher mating success when courtship dances were mutually exchanged, and when males sang. However, the sex initiating the courtship did not affect mating success. Most females produced CSDs after duet dancing but before hearing the entire song, indicating that duet dancing played a crucial role in mating. This finding highlights an unexplored aspect of duetting behaviour in the process of mutual mate choice. These results conflict with the majority of past songbird research, which has interpreted songs as primary behavioural sexual signals.